Adaptation of MacNew Heart Disease Health-Related Quality of Life Instrument in Indonesian Myocardial Infarction Patients - Devi Wulandari; Adriana Soekandar Ginanjar; Urip Purwono (Universitas Ahmad Dahlan, 2019)
AbstractLack of adapted health-related quality of life measurement in Bahasa Indonesia may create difficulties in concluding the effects of heart disease and its treatment on a patient's health-related quality of life in Indonesia. MacNew heart disease health-related quality of life questionnaire (MacNew) has been proven a valid and reliable health-related quality of life measurement. It also has been adapted in several languages. This study aimed at translating and assessing the Indonesian version of MacNew questionnaire validity evidence based on the relation with other variables on and internal consistency. Validity evidence based on the relation with other variables was assessed by correlating the Indonesian version of the MacNew questionnaire score with cardiac anxiety, gender, age, education level, left ventricular ejection fraction score, and comorbidity. Two hundred thirty-six patients diagnosed with myocardial infarction (MI) filled out the questionnaire at a one-time intake. Results from confirmatory factor analysis revealed three domains of health-related quality of life, namely emotional, physical, and social. The three-domain explained 42.31% of the health-related quality of life total variance. The internal consistency of the questionnaire was good (0.816-0.900). Health-related quality of life was negatively correlated with cardiac anxiety. Male patients had a higher health-related quality of life compare to female patients. However, there was no significant correlation between health-related quality of life and left ventricular ejection fraction and comorbidity. The Indonesian version of MacNew questionnaire demonstrated satisfactory psychometric properties and can be recommended to measure HRQOL in heart patients in Indonesia. Keywords: Health-related quality of life, MacNew Heart Disease HRQOL instrument, instrument adaptation